Asia, 1945-1954: Three Wars in One. - Álvarez, José Maurício (Advances in Social Sciences Research Journal, 2020)
The conflicts waged in Asia between 1945 and 1954 are examined here as part of the anti-colonial struggle and national independence, giving rise to free and original Asian practices. The background is the emergence and consolidation of the bipolar powers of the superpowers involved in the cold war. The decolonization of the region was part of the Western Allies’ ideals. However, the Cold Conflict’s political conveniences lead the Truman Administration to tolerate and support the colonial presence. American policy on Asia-Pacific feared that independence would jeopardize regional stability. This desideratum frustrated the aspirations of the local populations and elites and the communists. After 1949 starting its huge task of national reconstruction, the People’s Republic of China recovered imperial diplomatic practices. In addition to expanding his agricultural and industrial production bases, he supported the communist side in the war between the two Koreas and Vietminh, in Indochina. Exercising dominance over its allies the Maoist China, it consolidated its regional projection, suggesting to several important actors on the western side that the three conflicts were part of a single war against communism that they believed to be expanding.